Brachial Plexus Injury New Techniques and Ideas - Bahm, Jörg (IntechOpen, 2022)
In this book, specialists from different countries and continents share their knowledge and experience in brachial plexus surgery. It discusses the different types of brachial plexus injury and advances in surgical treatments.